Diasporas of the mind : Jewish and postcolonial writing and the nightmare of history - Cheyette, Bryan (Yale University Press, 2013)
In this fascinating and erudite book, Bryan Cheyette throws new light on a wide range of modern and contemporary writers - some at the heart of the canon, others more marginal - to explore the power and limitations of the diasporic imagination after the Second World War. Moving from early responses to the death camps and decolonization, through internationally prominent literature after the Second World War, the book culminates in fresh engagements with contemporary Jewish, post-ethnic and postcolonial writers.